Students’ Problem in Using English E-Learning in SMP Katolik 1 WR.Soepratman Samarinda - Erza Praditha; Dedi Rahman Nur (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This study intended to find out problems encountered by students when learning English through e-learning. This research is to find out what problems faced by students when learning English through E-Learning which is identified through a questionnaire distributed via Google forms to the students. The sample of this research was 86 students of the third-grade students of SMP Katolik 1 WR. In this study, the researcher computed the data used frequency distribution analysis to determine the percentage of the tendency of student's problems in internal or external factors when using e-learning in English learning. Both in terms of internal and external factors, each part is interrelated. The problem that happened with the teachers, then to the students, and eventually impacts the learning system which makes ineffective e-learning in the school, they are affecting each other and create a domino effect.